Trim27 interacts with Slx2, is associated with meiotic processes during spermatogenesis. Issue 19 (1st October 2016) - Zhuang, Xin-Jie; Tang, Wen-hao; Feng, Xue; Liu, Chang-yu; Zhu, Jin-liang; Yan, Jie; Liu, De-feng; Liu, Ping; Qiao, Jie
ABSTARCT: Formation of the XY body is believed to prevent recombination between X and Y chromosomes during meiosis. We recently demonstrated that SYCP3-like X-linked 2 (Slx2) could be involved in synaptonemal complex formation as well as XY body maintenance during meiosis. In order to further investigate the role and composition of XY body protein complexes in meiotic processes and spermatogenesis, a yeast 2-hybrid screening was performed, and the tripartite motif protein 27(Trim27) was found to interact with Slx2 and co-localized in the XY body. Trim27 has a tripartite motif (TRIM) consisting of a RING finger, B-box and coiled-coil domains, and is a transcriptional regulator that is expressed in various tumor cell lines. In this study, we showed that Slx2 and Trim27 were highly expressed in meiosis of mouse testis. And the Slx2/Trim27 interaction was confirmed in vivo by co-immunoprecipitation and mammalian 2-hybrid interaction assays. Moreover, cytoimmuno localization experiments revealed that Slx2/Trim27 was co-localized to the XY body of spermatocytes during meiosis, and immunohistochemical results revealed co-localization of Trim27 and γ-H2AX in the XY body of primary spermatocytes in the mouse testis. Trim27 may therefore be a transcriptional regulation protein connecting Slx2 and γ-H2AX, thereby promoting the formation of a more potent XY body protein complex in meiotic processes and spermatogenesis. In conclusion, Trim27 connecting Slx2 may regulate meiotic processes in multiple ways by influencing XY body formation and germ cell proliferation during spermatogenesis.